Urinary liver-type fatty acid-binding protein levels may be associated with the occurrence of acute kidney injury induced by trauma - Yasuda, Ryu; Suzuki, Keiko; Okada, Hideshi; Ishihara, Takuma; Minamiyama, Toru; Kamidani, Ryo; Kitagawa, Yuichiro; Fukuta, Tetsuya; Suzuki, Kodai; Miyake, Takahito; Yoshida, Shozo; Tetsuka, Nobuyuki; et al. (Frontiers in Medicine, 2024)
Introduction Acute kidney injury (AKI), with a fatality rate of 8.6%, is one of the most common types of multiorgan failure in the intensive care unit (ICU). Thus, AKI should be diagnosed early, and early interventions should be implemented. Urinary liver-type fatty acid-binding protein (L-FABP) could aid in the diagnosis of AKI. Methods In this prospective, single-center, observational study, we included 100 patients with trauma. Urinary L-FABP levels were measured using a semi-quantitative rapid assay kit 6 and 12 h after injury. Negative, weakly positive, and strongly positive urinary L-FABP levels were examined using two protocols. Using protocol 1, measurements were performed at 6 h after injury negative levels were considered “negative,” and weakly positive and strongly positive levels were considered “positive.” Using protocol 2, strongly positive levels at 6 h after injury were considered “positive,” and negative or weakly positive levels at 6 h after injury were considered “positive” if they were weakly positive or positive at 12 h after injury. Results Fifteen patients were diagnosed with AKI. Using protocol 1, the odds ratio (OR) was 20.55 (p = 0.001) after adjustment for the injury severity score (ISS), contrast media use, and shock index. When the L-FABP levels at 6 and 12 h were similarly adjusted for those three factors, the OR was 18.24 (p < 0.001). The difference in ORs for protocols 1 and 2 was 1.619 (p = 0.04). Discussion Associations between urinary L-FABP and AKI can be examined more precisely by performing measurements at 6 and 12 h after injury than only one time at 6 h.